ANALISIS DESAIN DISPOSAL PADA PENAMBANGAN PT. VALE INDONESIA, Tbk - Herichzon Tandiasa; Gina Audina P Alhabsyi; Syamsuddin; Hendra Sani (Journal Teknik Dan Teknologi, 2025)
PT Vale Indonesia Tbk (PTVI) is a subsidiary of Vale, a global mining company based in Brazil. Before being named PT Vale Indonesia Tbk, the company located in South Sulawesi was named PT International Nickel Indonesia Tbk. (PT INCO). The research problem is how to calculate the disposal design that requires later storage that can be used overburden material from the nearest Pit and the amount of geometry of each design that has been made. The method used to analyze using Vulcan software version 9.0, using formulas, interview methods and documentation. The results showed the total disposal design capacity of 12,213,531 (wmt), Disposal Storage Capacity of 18,791,082 (wmt) and Geometry s_disp_block_2g0_01: Slope Angle: 400, Number of Benches: 2 and Width of Storage: 40,791,082 (wmt) and Geometry s_disp_block_2g0_02: Slope Angle: 260, Number of Benches: 2 and Berm Width: 40m (40,835), Geometry s_disp_block_2g0_03: Angle of Slope: 340, Number of Benches: 2 and Width Width: 40m (40,835), Geometry s_disp_block_g04 Slope 450, Berm Width 42m (42,092), Number of Bench 5, 40 M), Slope Angle 450, Number of Benches 6, s_disp_block_2g0_05: Slope Angle: 340, Berm Width: 40,603 (41 M), Number of Benches 3. Number of overburden results from the nearest pit.